Adherence to the Mediterranean diet in Italian school children (The ZOOM8 Study). (August 2014) - Roccaldo, Romana; Censi, Laura; D'Addezio, Laura; Toti, Elisabetta; Martone, Deborah; D'Addesa, Dina; Cernigliaro, Achille; the ZOOM8 Study group; Censi, Laura; D'Addesa, Dina; D'Amicis, Amleto; Angelini, Veronica; et al.
Abstract The adherence to the Mediterranean diet (MD) of 1740 Italian 8–9-year-olds was evaluated using the KIDMED index and a descriptive analysis of it by socio-demographic and lifestyle factors was performed. Only 5.0% of the children resulted "high" adherers of MD (62.2% "average" and 32.8% "poor"). This scarce adherence was due to a low consumption of fruit, vegetables, legumes, dairy products and a high intake of commercially baked goods for breakfast and sweets. Hindrances to fruit, vegetables and pulses consumption were reported for one-third of the sample. The adherence rates did not differ significantly with BMI and gender. Adherence improved with: having lunch at school; liking lunch at school; breakfast with family; no free access to food; availability of fruit and pulses; liking vegetables; higher maternal education; lower child screen time; population size of place of residence. The results show it is important to improve family food habits and dietary knowledge.